Real-time vascular monitoring of PDLs and IPL for vascular treatment: effects of fluence and pulse duration on a rabbit ear model - Tun Tun Aung; Yusang Hu; Xiaohan Liu; Manmei Long; Wanyi Wang; Khin Maung Htwe; Soe Lei May; Yuhao Sun; Yixin Zhang; Zheng Zhang (Frontiers in Medicine, 2026)
Background Pulsed dye lasers (PDLs) and intense pulsed light (IPL) are commonly used for treating cutaneous vascular diseases but lack standardized and reproducible treatment protocols. Reliable vascular models are needed to visually assess posttreatment responses. Methods Sixteen male rabbits were divided into two groups, with each ear subdivided into three treatment regions. PDL treatment was applied with pulse durations of 0.45 ms (fluences: 4, 5.5, and 8 J/cm 2 ) and 1.5 ms (fluences: 5.5, 8, and 13 J/cm 2 ). IPL was applied in single-pulse (10, 13, and 15 J/cm 2 ) and double-pulse (10, 13, 17, and 20 J/cm 2 ) modes. Vascular morphology and blood flow were evaluated using photographs and laser speckle contrast imaging (LSCI) before treatment, immediately after treatment, on days 1, 3, 5, 7, and 14. Histopathological analysis was performed 24 hours posttreatment. Statistical analysis was conducted with two-way ANOVA and Tukey's test, with P < 0.05 considered to indicate statistical significance. Results The dorsal ear vessels of rabbits consisted of longitudinally arranged main blood vessels (MBVs) and fan-shaped branch blood vessels (BBVs), with diameters ranging from 150–300 μm and 90–120 μm, respectively. In the PDL treatment, effective vessel closure with limited peripheral tissue damage was achieved using 0.45 ms at 5.5 J/cm 2 for BBVs, whereas 1.5 ms at 8.0 J/cm 2 was associated with qualitative evidence of more sustained MBV closure. In the IPL treatment, a single pulse at 13.0 J/cm 2 effectively closed the branch vessels, whereas the double-pulse mode primarily induced vessel dilation. Conclusion The rabbit ear vascular model, combined with dermoscopy, LSCI, and histopathology, provides a reproducible multimodal platform for longitudinal evaluation and systematic parameter screening, offering a reliable preclinical foundation for comparative assessment and protocol refinement prior to clinical translation.